The prodromal individuals’ perspective on active recruitment for early detection of α-synucleinopathies - Sinah Röttgen; Eva Schaeffer; Annette Rogge; Ramona Hartung; Konstantin Kufer; Gereon R. Fink; Daniela Berg; Anja Ophey; Michael Sommerauer (npj Parkinson's Disease)
Abstract Only the timely detection of individuals with incipient α-synucleinopathies can pave the way for developing disease-modifying therapies. Our aim was to explore the views of individuals with isolated REM sleep behavior disorder (iRBD), actively recruited from the general population, on the ethical justifiability of active recruitment and their experiences with risk disclosure. This mixed-methods study surveyed individuals with iRBD, confirmed by video-polysomnography, utilizing an interdisciplinary-developed online questionnaire. Of 99 invited individuals, 75 (75.8%) answered the survey. While 55.6% experienced the information on the increased risk as burdensome, 63.9% supported risk disclosure if consent had been obtained beforehand. Almost all individuals (96.2%) regarded our active recruitment method as appropriate, and 86.7% indicated they would participate again. Open-text responses indicated that key motivations included access to information and care, and contributing to research progress. This well-received recruitment strategy could serve as a model for future screening initiatives in α-synucleinopathy research.